(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, increasing the share of the textile industry in the economy, increasing the volume and quality of textile products produced in the country, further improving the standardization and certification system in the textile industry,the implementation of the cluster model of textile industry development was considered.